A systematic review of barriers impeding the implementation of government green procurement. Issue 4 (19th October 2020) - Vejaratnam, Navarani; Mohamad, Zeeda Fatimah; Chenayah, Santha
Abstract : Purpose: Government green procurement (GGP) is becoming a popular environmental policy instrument to spur the economy whilst protecting the environment. However, the implementation of GGP is impeded by various barriers. This paper aims to analyse the existing literature on barriers impeding GGP. Design/methodology/approach: This systematic literature review was guided by the PRISMA Statement (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) review method. A total of 29 articles from the Scopus and Web of Science databases were selected for the review. Findings: Five themes, i.e. finance, legal, people, knowledge and organisation, emerged from this review, which further produced 16 sub-themes. Lack of knowledge and awareness were the major barriers for GGP, while financial constraint was not the major barrier for GGP, as previously perceived. Barriers related to organisation were the most complex. Certain barriers were found more in developed or developing countries. Research limitations/implications: Only article journals with empirical data were selected. Review articles, book series, books, chapters in books and conference proceedings were excluded. Practical implications: Public managers should place highest priority to enhance knowledge and awareness of procurers on GGP. Other important initiatives to be undertaken include emulating best practices, implementing change management and incentivising suppliers to tackle the prevalent barriers of GGP. Finally, with increasing evidences on barriers related to GGP, public managers should consider mapping and analysing specific barriers hindering GGP in their organisation/country. Social implications: A less challenging and efficient implementation of GGP contributes to a cleaner environment. Originality/value: This article will be the first to systematically review the barriers of GGP.